2014
DOI: 10.1371/journal.pone.0109062
|View full text |Cite
|
Sign up to set email alerts
|

How Modification of Accessible Lysines to Phenylalanine Modulates the Structural and Functional Properties of Horseradish Peroxidase: A Simulation Study

Abstract: Horseradish Peroxidase (HRP) is one of the most studied peroxidases and a great number of chemical modifications and genetic manipulations have been carried out on its surface accessible residues to improve its stability and catalytic efficiency necessary for biotechnological applications. Most of the stabilized derivatives of HRP reported to date have involved chemical or genetic modifications of three surface-exposed lysines (K174, K232 and K241). In this computational study, we altered these lysines to phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Computational chemistry on hemeproteins has been widely used , and proved to be a good strategy to describe molecular details concerning hemic systems and as a prediction tool of relevant biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry on hemeproteins has been widely used , and proved to be a good strategy to describe molecular details concerning hemic systems and as a prediction tool of relevant biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…57, 58 In addition, its relatively small physical size is ideal for probing the efficiency of a covalent attachment to a bioink scaffold, enabling easy distinction between sole physical entrapment and covalent anchoring. Since HRP only presents 6 free amino residues on its surface, 59 we aimed to introduce as many methacrylate groups as possible.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have demonstrated that the modification of the surface of functional proteins can modulate their native activity [5–7] . The modification of the primary sequence of the protein can give rise to several scenarios: from the complete inactivation of the protein to a significant enhancement of its performance.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Several reports have demonstrated that the modification of the surface of functional proteins can modulate their native activity. [5][6][7] The modification of the primary sequence of the protein can give rise to several scenarios: from the complete inactivation of the protein to a significant enhancement of its performance. Among all the combinations of functional proteins and artificial materials, the particular case of enzymes modified with polymers requires detailed investigation.…”
Section: Introductionmentioning
confidence: 99%